HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN PENYESUAIAN SOSIAL PADA MAHASISWA D III ALIH PROGRAM PKN STAN - Syamatha Puspa Devi; Dinie Ratri Desiningrum (Jurnal EMPATI, 2017)
Every human being undergoes a transition to his new environment. When they become students, they will move from school to school or work to school, which requires social skills. This study aims to determine the relationship between emotional and social adjustment of the first year Diploma III transform program student PKN STAN. The subject of this research is the third student of the first year Diploma III transform program student PKN STAN. The sample used 145 students with cluster sampling technique. The measuring instrument used is the emotional intelligence scale (33 valid items, with α = .85) and Social Adjustment Scale (45 valid items, with α = .92) that have been tested in 110 of the first year Diploma III transform program student PKN STAN. The simple regression coefficient between emotional intelligence and social adjustment is 0.83 with p = 0,000 (p <.001). These results indicate the hypothesis proposed by the Researcher, that there is a positive relationship between emotional intelligence and social adjustment of the first year Diploma III transform program student PKN STAN is acceptable. Value of the coefficient of determination of .70 means that emotional intelligence has an effective contribution of 70% in improving student social adjustment, while the remaining 30% is determined by other factors not measured in this study. Suggestions for future researchers to examine other factors of social adjustment.